Makna Toleransi dan Persepsi terhadap Keberagaman Indonesia Melalui Kegiatan Modul Nusantara Pada Mahasiswa PMM 4 Inbound Universitas Jember - Rina Gustina; Ahmad Hasannul Hakim; Muhammad Rafi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
The Nusantara Module is one of the compulsory courses for students who take part in the Independent Student Exchange program. The content of the Nusantara module is social contribution, diversity, inspiration and reflection. The purpose of this research is to find out how tolerant and perceived Indonesian cultural diversity through Nusantara module activities for PMM 4 Inbound students of Jember University. The research method used is a qualitative research method, using the theory of symbolic interactionism of George Herbert Mead's thought. The results showed that the Nusantara Module course has a role in increasing the cultural tolerance attitude of inbound students of Jember University through; first, respecting and respecting diversity; second, preventing the emergence of ethnocentrism and in the Nusantara Module there are symbols used by Inbound students in interacting in order to implement tolerance attitudes and values.